2008
DOI: 10.1038/pcan.2008.36
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of body mass index and serum testosterone with disease outcomes in men with castration-resistant metastatic prostate cancer

Abstract: The purpose of this study was to evaluate the relationship of baseline body mass index (BMI) and serum testosterone level with prostate cancer outcomes in men with castration-resistant metastatic prostate cancer (CRPC). BMI and testosterone levels were evaluated for their ability to predict overall survival (OS) and prostate-specific antigen (PSA) declines in the TAX327 clinical trial, an international phase III randomized trial of one of the two schedules of docetaxel and prednisone compared with mitoxantrone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…However, many of the previous studies have focused on patients within the overweight or obese BMI ranges [25], whereas the present study features a weightlosing male cohort with a median BMI within the healthy range. The present study is in accordance with other reports that have documented low testosterone levels in anorectic males [26] and high testosterone levels in obese patients with prostate cancer [27]. Thus, hypogonadism could represent an important mechanism of weight loss.…”
Section: Discussionsupporting
confidence: 94%
“…However, many of the previous studies have focused on patients within the overweight or obese BMI ranges [25], whereas the present study features a weightlosing male cohort with a median BMI within the healthy range. The present study is in accordance with other reports that have documented low testosterone levels in anorectic males [26] and high testosterone levels in obese patients with prostate cancer [27]. Thus, hypogonadism could represent an important mechanism of weight loss.…”
Section: Discussionsupporting
confidence: 94%
“…A full-text review was performed for 178 potentially relevant articles. After evaluating the selection criteria, we identified 11 articles with 4206 patients for systematic review and ten articles with 4136 patients for meta-analysis [8][9][10][23][24][25][26][27][28][29][30]. Figure 1 depicts the selection process and list.…”
Section: Literature Searchmentioning
confidence: 99%
“…In this sense, we have recently uncovered the existence of a fine, germane crosstalk between the endocrine‐metabolic status and the development and homoeostasis of the prostate gland, wherein key components of the insulin, IGF1 and adipokines axes, among other, could play a relevant pathophysiological role . In addition, it has been suggested that low levels of testosterone could be linked with the presence of abdominal obesity, and this in turn, might cause an alteration in the metabolism of fatty acids promoting insulin resistance, which might be associated to PCa risk; however, the association between circulating testosterone levels, metabolic status and PCa progression/aggressiveness remains controversial . Furthermore, circulating levels of CRP, one of the most useful markers to assess varying degrees of inflammation in disease states such as obesity, diabetes mellitus (DM), etc., have been found to be elevated in patients with different cancer types compared to healthy patients; but the putative association between CRP levels, metabolic status, testosterone and PCa remains still unknown …”
Section: Introductionmentioning
confidence: 99%